Kicz i styl - Paszek, Jerzy (Stylistyka, 1994)
The author considers the-notion of trash in literature, including among its characteristic features "hypercorrectness" of form and style, mistakes in style and a stylistic "cheering", that is a certain kind of intertextual usurpation.